A efetividade da Lei Maria da Penha em Belém: um estudo sobre a concessão e a execução das medidas protetivas de urgência - VIDAL, Vivian Gavinho (Universidade Federal do Pará, 2017)
The proposal of this work is realize a study about the women victims of domestic violence access to justice on Belem city. The bases of this study are the constitutionals provisions related to access to justice that not satisfy only with the warranty to actuate the Judiciary to interfere in a conflict initiated. The internal legal order, founded as Democratic State of Law, determines that all the citizens should be assure to access with a fair legal order that promotes effectiveness of the judicial decisions, providing the effective exercise of right. Considering the inequalities in Brazilian society, a gender category will be used as a way of understanding the differences existing between men and women, between men and women. Thus, the gender also allows the design of new perspectives on violence against women and the way the state deals with this theme. The concession and implementation of urgent protective measures laid out in law 11.340/06 are the specifics objects of this work. The protective measures are instruments adopted by the law that purpose to prevent the occurrence of new aggressions against women, safeguarding their rights to life and physical safety, psychological and moral From the nature of urgent protective measures will be checked for applicability of the Maria Penha law in Belem with observation the production of the actual effects of its concession in the lives of women who seek protection in the judicial protection.